Flotation performance of chalcopyrite in the presence of an elevated pyrite proportion. (February 2022) - Lee, Richard Li Jie; Chen, Xumeng; Peng, Yongjun
Highlights: Chalcopyrite became more anodic after being contacted with pyrite. A larger surface pyrite/chalcopyrite ratio led to a stronger galvanic interaction. Chalcopyrite flotation was compromised by 5% pyrite but restored by 25% pyrite. Pyrite flotation was enhanced with an increase in pyrite proportion. Chalcopyrite or pyrite flotation was controlled by the galvanic interaction. Abstract: Recently, the copper industry is facing a challenge in dealing with low-grade copper ores and the flotation performance deteriorates when a copper ore with an elevated pyrite proportion is processed. This study investigated the effect of pyrite proportion on chalcopyrite and pyrite flotation via a tri-mineral system (chalcopyrite-pyrite-quartz) with a fixed Cu head grade while varying the pyrite proportion. Electrochemical studies revealed that the overall corrosion current of chalcopyrite-pyrite galvanic interaction increased with the increase of pyrite surface area, boosting the anodic role of chalcopyrite. Flotation results showed that both Cu grade and Cu recovery decreased by the introduction of 5% pyrite, but Cu recovery was restored by the introduction of 25% pyrite. Collectorless flotation, EDTA extraction and pulp chemistry measurement indicated that chalcopyrite and pyrite flotation behaviours at different pyrite proportions were governed by the galvanic interaction between chalcopyrite and pyrite which controlled chalcopyrite oxidation and copper activation on pyrite.